LOCAL ELECTIONS TO REGIONAL AND CITY COUNCILS: COMPARATIVE ANALYSIS OF RESULTS - Гнатенко, П. Г. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2019)
The results of elections to regional councils and city councils of regional centers in 2015 in Ukraine are analyzed in the context of transformation of the electoral system. The paper is mainly focused on such indicators as the percentage of votes received, the number and percentage of deputy seats received in the respective councils. Additionally, such indicators as the number of local party organizations that passed to the relevant councils are analyzed; the all-Ukrainian statistics regarding the share of mandates received by concrete parties, as well as the frequency with which particular parties earned the first place in the number of mandates received in each of the councils is summarized. Uprising regionalization of political system in Ukraine caused by growing role of local leaders and their power to influence political processes in regions is defined. The results obtained are compared at the level of regional councils and city councils of regional centers, as well as between political parties of different levels. The conclusion on effectiveness of local political parties in comparison to large national ones in the regions is made. There are «parties of cities» and «parties of regions», which significantly differ in their level of support within the regional centers and regions in general; parties with a relatively common level of support are determined as well. In terms of aggregated indicators, it is concluded that city councils of regional centers are more successful ones for ballot strategies from non-parliamentary parties; on the other hand, parliamentary parties give a significant advantage to their representatives at the level of regional elections. In such circumstances, respectively, candidates need different strategies for elections to city councils of regional centers and regional councils; in many cases, the winning strategy was to run from the party, which was represented by the current mayor or another local candidate with sufficient support and resource support. The paper points the weakening of traditional geopolitical conflicts for Ukraine, which are replaced by more fragmented oppositions - for example, at the regional level.